Gross and Morphometric Evaluation of Deltoideus Muscle of Cattle and One-Humped Camel - I. J. Gosomji, S. A. Hena,; Sonfada, M. L.; Sonfada, M. L.; F.E, Sa’ayinzat (International Journal of Innovative Research in Medical Science, 2017)
The study was conducted using 25 forelimbs each obtained from male camels (Camelus dromedarius) and cattle (Zebu type) purchased from Sokoto Municipal Modern abattoir. The animals were within the ages of 6 months, 1year, 3years, 5 years and 7 years. The forelimbs were dissected and deltoideus identified and measured. Morphologically, the scapular part of the deltoideus in cattle appeared paler in contrast to it acromial counterpart, as well as when compared to the camel’s deltoideus. The morphometric parameters showed increased values along age especially in camels. Considering the variables obtained in deltoideus architecture, it therefore concluded that the deltoideus of cattle seems to have greater potential production force than the camel.